The role of financial globalization in the long-run volatility between forex and stock markets during COVID-19: Evidence from Africa - Michael Insaidoo; William Gabriel Brafu-Insaidoo; James Atta Peprah; William Godfred Cantah (Research in Globalization)
This study examines the long-run volatility between forex and stock markets and the role of financial globalization in this relationship in Africa, during the COVID-19 pandemic period, using panel Fully Modified Ordinary Least Squares (FMOLS) and panel Dynamic Ordinary Least Squares (DOLS) approaches. Our empirical outcomes revealed bi-directional long-run volatility between the two financial markets in the COVID-19 pandemic period. The results further established that, financial globalization reduces forex markets’ volatility effects on stock markets’ volatility, whilst it heightens stock markets’ volatility effects on forex markets’ volatility in Africa, during the COVID-19 pandemic period. The implications of this study, include the need to harness the stabilising potential of financial globalization in the long-run volatility between forex and stock markets, primarily through asset diversification, enhanced information flow, and market efficiency in African financial markets.